INFLUENCE OF ISLAMIC SOCIAL REPORTING (ISR) DISCLOSURE ON THE QUALITY OF PROFITS IN REGISTERED COMPANIES IN JAKARTA ISLAMIC INDEX (JII) - Sadli, Nurhemifitrah; Semaun, Syahriyah; Sahara, Ira (Institut Agama Islam Negeri Parepare, 2024)
Islamic Social Reporting (ISR) is one way to demonstrate full disclosure in an Islamic context. Earnings quality refers to the extent to which a company's reported earnings reflect its true economic performance. This research aims to determine the influence of the independent variable, namely Islamic Social Reporting, on the dependent variable, namely Profit Quality, and to find out how big it isThe influence of Islamic Social Reporting disclosure on Profit Quality in companies listed on the Jakarta Islamic Index. This research uses research methodsquantitative, associative approach, with field research. The data used in this research is in the form of company annual reports on the Indonesia Stock Exchange for 2019-2021. In collecting data, this research uses two methods, namely count analysis and dummy variables. The analysis technique used is simple linear regression. The results of this research show that the Islamic Social Reporting disclosure score is more than 59%, which means that the disclosures made have reached more than 48 disclosure score items. Meanwhile, the average value of earnings quality reached 2.8388. The results of the Spearman rank correlation test show that there is a fairly strong relationship between the Islamic Social Reporting variable and earnings quality. The results of testing the coefficient of determination show that the ability of the independent variable in this study to influence the dependent variable is only 9.9%. Furthermore, the partial test results show that Islamic social reporting disclosure has a positive and significant effect on earnings quality with a significance value of 0.008 <0.05. By implementing Islamic Social Reporting, companies not only focus on achieving maximum profits, but also pay attention to the social and environmental impacts of their business activities. This can attract the interest of investors, especially Muslim investors, to invest in the company.